Enhancing commercial check valves in downhole pump applications through laboratory testing system development - Weerachai Chaiworapuek; Juthanee Phromjan; Kittipat Wejwittayaklung; Ravivat Rugsaj; Chakrit Suvanjumrat (Results in Engineering)
In this study, we aim to enhance the performance and longevity of downhole pumps employed in crude oil extraction in the oil industry. Downhole pumps play a pivotal role in the rod-pump system, comprising traveling and standing valves that function similarly to ball check valves. However, these valves often experience premature wear and tear. To address this concern, we embarked on experiments involving various check valve alternatives to conventional ball valves within downhole pumps. The testing conditions were controlled precisely. Furthermore, we evaluated four distinct check valve types, the original (representing the incumbent ball valves), spring-poppet (C), spring-ball (CB), and spring-poppet with soft-seated (S6C) check valves, within a controlled laboratory environment. We employed a TEXAPON N70 solution to replicate the properties and temperature conditions of crude oil. A portable ultrasonic flow meter was used to quantify the pump flow rate and assess its volumetric efficiency. In addition, we recorded data on the polished-rod load and plunger displacement to generate dynamometer cards, thereby enabling a comprehensive evaluation of the operational performance of the pump. Furthermore, we conducted a vacuum test to scrutinize valve leakage, which is a crucial indicator of the operational lifespan of a downhole pump. Our findings show that incorporating the CB check valve with the RHB pump in oil wells operated by the PTT Exploration and Production Public Company Limited (PTTEP) could result in a 15 % increase in volumetric efficiency and a remarkable 160 % improvement in durability compared to the original ball check valve.